Influence of Education and Skills Level on Generation Z Employee Performance at PT Solomon Indo Global - Zebua, Siles; Suwaji, Rifiki (PT Mattawang Mediatama Solution, 2025)
This research aims to determine the influence of education level and job skills on the performance of Generation Z employees at PT Solomon Indo Global. As the youngest demographic in the workforce, Generation Z possesses unique characteristics shaped by digital exposure and technological adaptability. However, there remains debate regarding whether formal education alone can significantly impact work performance, especially in industrial settings. This study uses a quantitative approach with a population of 83 Gen Z employees, all selected using a saturated sampling technique. Data were collected through a structured questionnaire and analyzed using multiple linear regression with SPSS version 26. The results showed that the education level variable has a positive but not statistically significant effect on employee performance (Sig. = 0.073 > 0.05; t = 1.814), suggesting that formal education alone is not a direct determinant of workplace effectiveness. Meanwhile, the skills variable had a strong and significant positive effect (Sig. = 0.000 < 0.05; t = 14.067), highlighting the importance of both technical and soft skills in improving individual productivity. Simultaneously, the F-test confirmed that both variables together significantly influence performance (F = 177.750; Sig. = 0.000), with an R² value of 0.812, meaning 81.2% of the variation in employee performance can be explained by education and job skills. These findings suggest that companies must integrate education and skills training in their HR development programs. For Generation Z to thrive in competitive work environments, strategies must go beyond formal education and emphasize continuous skill enhancement aligned with industrial needs.